Principle of chemical analysis - Mohd Marsin Sanagi; Azli Sulaiman; Wan Aini Wan Ibrahim; Aemi Syazwani Abdul Keyon (Penerbit UTM Press, 2017)
This book has been written with a main objective of instilling the understanding of basic principles of quantitative analytical chemistry and how the principles are utilized in analytical laboratory. The scope of this work covers the fundamentals of chemical analysis . Thorough exposures to these fundamentals, students will have a strong footing to perform numerous procedures in chemical analysis.